The Many Faces of Enterococcus spp.—Commensal, Probiotic and Opportunistic Pathogen - Beata Krawczyk (Microorganisms, 2021)
Enterococcus spp. are Gram-positive, facultative, anaerobic cocci, which are found in the intestinal flora and, less frequently, in the vagina or mouth. Enterococcus faecalis and Enterococcus faecium are the most common species found in humans. As commensals, enterococci colonize the digestive system and participate in the modulation of the immune system in humans and animals. For many years reference enterococcal strains have been used as probiotic food additives or have been recommended as supplements for the treatment of intestinal dysbiosis and other conditions. The use of Enterococcus strains as probiotics has recently become controversial due to the ease of acquiring different virulence factors and resistance to various classes of antibiotics. Enterococci are also seen as opportunistic pathogens. This problem is especially relevant in hospital environments, where enterococcal outbreaks often occur. Their ability to translocate from the gastro-intestinal tract to various tissues and organs as well as their virulence and antibiotic resistance are risk factors that hinder eradication. Due to numerous reports on the plasticity of the enterococcal genome and the acquisition of pathogenic microbial features, we ask ourselves, how far is this commensal genus from acquiring pathogenicity? This paper discusses both the beneficial properties of these microorganisms and the risk factors related to their evolution towards pathogenicity.